Effects of sequential paclitaxel–carboplatin followed by gemcitabine-based chemotherapy compared with paclitaxel-carboplatin therapy administered to patients with advanced epithelial ovarian cancer: A retrospective, STROBE-compliant study. Issue 51 (December 2016) - Wang, Fei; Du, Xuelian; Li, Xiaoxia; Liu, Naifu; Yu, Hao; Sheng, Xiugui
Abstract : Abstract: We aimed to compare the efficacy of paclitaxel and carboplatin followed by gemcitabine-based combination chemotherapy with paclitaxel–carboplatin for treating advanced epithelial ovarian cancer in this retrospective, STROBE-compliant study. Patients' tolerance to treatment was also assessed. We retrospectively analyzed the records of 178 women who underwent initial optimal debulking surgery between January 2003 and December 2011 to treat FIGO stage IIIc epithelial ovarian cancer. Patients in arm 1 (n = 88) received 4 cycles of paclitaxel and carboplatin followed by 2 to 4 cycles of gemcitabine-based combination chemotherapy. Patients in arm 2 (n = 90) received 6 to 8 cycles of paclitaxel and carboplatin. The granulocyte-colony stimulating factor was administered prophylactically to all patients. The median follow-up for both arms was 62 months. Medianprogression-free survival (PFS) between arms 1 and 2 (28 and 19 months [ P  = 0.003]) as well as 5-year OS (34.1% and 18.9% [ P  = 0.021]) differed significantly. The neurotoxicity rate was significantly higher in arm 2 than in arm 1 (45.2% vs 27.1%, P  = 0.026). There was no significant difference between study arms in hematological toxicity. The sequential regimen significantly improved PFS and 5-year OS with tolerable toxicity compared with the single regimen, and offers an alternative for treating patients with advanced epithelial ovarian cancer.